Requirements of older adults for a daily use of an internet-based cognitive training platform. (March 2015) - Haesner, Marten; O'Sullivan, Julie L.; Gövercin, Mehmet; Steinhagen-Thiessen, Elisabeth
Abstract : A decline of cognitive abilities is a part of normal human ageing. However, recent research has demonstrated that an enriched environment can have a beneficial impact on cognitive function in old age. Accordingly, mentally and socially active lifestyles are associated with less cognitive decline in old age. Specific interventions such as computerized cognitive training programs for older adults are also known to have a positive effect on the level of cognitive functioning. Therefore, online platforms combining cognitive training with web 2.0 features may yield multiple benefits for older users. However, to date only little research exists on technological acceptance and media use in this age-group especially for cognitively-impaired seniors. Therefore, in order to assess specific preferences and potential barriers of older adults regarding a web-based platform for cognitive training, we conducted qualitative interviews with 12 older adults. Half of the participants were diagnosed with mild cognitive impairment (MCI). Most importantly, our results show that cognitive exercises should incorporate themes and topics older adults are interested in. Additional communication features could serve as ideal methods for increasing user motivation. Furthermore, we derived eight critical requirements of older adults concerning daily use of a web-based cognitive training platform. Implications for future research and development are discussed.